2020
DOI: 10.1038/s41598-020-69632-5
|View full text |Cite
|
Sign up to set email alerts
|

CD122-targetted IL-2 signals cause acute and selective apoptosis of B cells in Peyer’s Patches

Abstract: Interleukin-2 (IL-2) has both pro- and anti-inflammatory properties that have been harnessed clinically and that are used experimentally to modulate leukocyte subsets in vivo. In mice, the bioavailability and half-life of IL-2 in vivo can be increased by complexing recombinant IL-2 with different clones of anti-IL-2 monoclonal antibodies that differentially target the cytokine to cells expressing different kinds of IL-2 receptors. While the impacts of systemic IL-2: anti-IL-2 antibody complex (IL-2C) administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
1
Order By: Relevance
“…Further, it has recently been shown that gut leukocytes, such as intraepithelial lymphocytes and γδ-T cells, have effects on metabolism [36,37]. A recent report on the effects of IL-2/S4B6 on gut leukocytes demonstrated no difference in numbers of intraepithelial lymphocytes in treated mice [38], suggesting that modulation of these cells is not key for reducing cholesterol levels in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Further, it has recently been shown that gut leukocytes, such as intraepithelial lymphocytes and γδ-T cells, have effects on metabolism [36,37]. A recent report on the effects of IL-2/S4B6 on gut leukocytes demonstrated no difference in numbers of intraepithelial lymphocytes in treated mice [38], suggesting that modulation of these cells is not key for reducing cholesterol levels in our study.…”
Section: Discussioncontrasting
confidence: 49%